Α‐Isocupreine, an Enantiocomplementary Catalyst of β‐Isocupreidine. Issue 38 (26th August 2013) - Nakamoto, Yoshito; Urabe, Fumiya; Takahashi, Keisuke; Ishihara, Jun; Hatakeyama, Susumi
<x xml:space="preserve">Abstract</x> Complementary chemistry! α‐Isocupreine (α‐ICPN) was synthesized for the first time in one step from quinine by treatment with CF3SO3H (see scheme). This compound serves as an enantiocomplementary catalyst to β‐isocupreidine (β‐ICD) in the Morita–Baylis–Hillman reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>